2016
DOI: 10.1111/ajt.13853
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Utilization and Clinical Outcomes for Belatacept- and Tacrolimus-Based Immunosuppression in Renal Transplant Recipients

Abstract: The performance of belatacept in a real clinical setting has not been reported. A retrospective cohort study was conducted using registry data comparing 1-year clinical outcomes between belatacept- and tacrolimus-treated adult kidney transplant recipients (KTRs) from January 6, 2011, through January 12, 2014. Of 50 244 total patients, 417 received belatacept plus tacrolimus, 458 received belatacept alone, and 49 369 received tacrolimus alone at discharge. In the overall study cohort, belatacept alone was assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 9 publications
2
23
0
Order By: Relevance
“…Details of the combined belatacept/tacrolimus regimens are contained in figures 1 and 2 and are similar to a regimen that has been previously reported. (14) In short patients receiving Bela/Tac Short regimen were treated with a modified belatacept regimen which eliminated doses at days 4 and 14. They also received tacrolimus twice daily to achieve trough doses 8-12ng/ml from the day of transplant through the first three months and then tapered over the next two months to end by 5 months post-transplant.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the combined belatacept/tacrolimus regimens are contained in figures 1 and 2 and are similar to a regimen that has been previously reported. (14) In short patients receiving Bela/Tac Short regimen were treated with a modified belatacept regimen which eliminated doses at days 4 and 14. They also received tacrolimus twice daily to achieve trough doses 8-12ng/ml from the day of transplant through the first three months and then tapered over the next two months to end by 5 months post-transplant.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, the accumulation of CD4 + and CD8 + T cells in the allograft was further reduced in the combination therapy group compared with monotherapy groups, and approached numbers that were comparable to naive tolerant allografts ( Figure 6A). We also tested whether FTY720 plus CTLA4-Ig reduced donor-specific infiltrating T cells by using sensitized mice that harbored, from the time of donor spleen cell sensitization, a tracer population of donor-reactive T cell receptor-transgenic TCR75 cells (1,000-2,000 cells/mouse) with specificity for donor-derived peptide (K d [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68] ) presented on recipient I-A b . We similarly observed that the combination FTY720 plus CTLA4-Ig significantly decreased the numbers of TCR75 cells (which were predominantly CD44 + CD62L -) infiltrating the allografts compared with CTLA4-Ig monotherapy ( Figure 6B).…”
Section: Ctla4-ig Fails To Inhibit the Accumulation Of T Cells Into Tmentioning
confidence: 99%
“…Indeed, we observed that the efficacy of CTLA4-Ig was inferior in recipients that were more recently sensitized and harbored higher levels of DSA. In initial trials with belatacept that involved nonsensitized recipients and current clinical use involving patients that do not meet this stringent criteria, higher rates of acute rejection have been reported (2,34,(57)(58)(59). Thus, we consider the more stringent model with low levels of circulating DSA an excellent model to investigate CTLA4-Ig efficacy.…”
Section: Cd4mentioning
confidence: 99%
“…Despite improved graft function and metabolic complications with belatacept alone, it was advised to add short-term tacrolimus in the first year posttransplant and consider lymphocyte induction in patients with high rejection risk. 75 …”
Section: Costimulation Blockadementioning
confidence: 99%